2021
DOI: 10.1093/nar/gkab500
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex binders as cytostatic modulators of innate immune genes in cancer cells

Abstract: G-quadruplexes (G4s) are non-canonical nucleic acid structures involved in fundamental biological processes. As G4s are promising anticancer targets, in past decades the search for effective anticancer G4 binders aimed at the discovery of more cytotoxic ligands interfering with specific G4 structures at oncogenes or telomeres. Here, we have instead observed a significant activation of innate immune genes by two unrelated ligands at non-cytotoxic concentrations. The studied G4 binders (pyridostatin and PhenDC3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 70 publications
9
56
0
Order By: Relevance
“…In particular, DDLPS cells exposed to an equitoxic concentration of RHPS4 were characterized by a marked accumulation of micronuclei, which exhibited extensive DNA damage in a significant proportion, as suggested by the positive staining for the phosphorylated form on Ser139 of histone H2AX [ 41 ]. Notably, this evidence corroborates the notion that micronuclei may form in the presence of dysfunctional telomeres [ 42 ], as well as recent findings showing that distinct G4 ligands may trigger the formation of micronuclei in different human tumor cells [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In particular, DDLPS cells exposed to an equitoxic concentration of RHPS4 were characterized by a marked accumulation of micronuclei, which exhibited extensive DNA damage in a significant proportion, as suggested by the positive staining for the phosphorylated form on Ser139 of histone H2AX [ 41 ]. Notably, this evidence corroborates the notion that micronuclei may form in the presence of dysfunctional telomeres [ 42 ], as well as recent findings showing that distinct G4 ligands may trigger the formation of micronuclei in different human tumor cells [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, cGAS has been also found to localize at DNA bridges, which represent markers of telomere dysfunctions, thus raising the possibility that G4 binder-mediated dysfunctional telomeres may also play a role in innate immune signaling [ 42 ]. Noteworthily, enhanced micronuclei formation in breast cancer cells exposed to G4 binders has been recently reported to trigger the activation of innate immune genes (i.e., type I interferon genes) via cGAS-STING [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the dual role in cancer of this pathway is known since it can promote or inhibit tumorigeneses according to the biological context [ 38 ]. A previous study showed that STING pathway was induced by PDS in MCF-7 cells [ 39 ]. In agreement with this study, we observed that G4 ligands slightly increased STING expression and the effect was maintained with the virus and the combinatory treatments (although without reaching statistical significance).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, G4 stabilizers such as pyridostatin and PhenDC3 (Figure 6) have also been shown to promote type I interferon production and innate immune gene activation, which could be helpful in combination immunotherapies for unresponsive tumors [105]. 2 and 3.…”
Section: Gtc365 (Acridine)mentioning
confidence: 99%